The work process in Primary Health Care and leprosy control: integrative review (Research, Society and Development, 2023)
The structuring of the work process is crucial in Leprosy Control Actions (LCA), and this review aimed to evaluate the work process of Primary Health Care (PHC) professionals for the LCA. Integrative review in four databases: MEDLINE Complete, Scielo, SCOPUS and Web of Science using the descriptors “leprosy” and “primary health care”. An in-depth analysis of 30 articles was carried out through reading, filing and organization of the results in thematic analysis. Three main categories were evidenced in the evaluation of the work process for the LCA: I – General characteristics of the work process in the LCA; II - Structure: Physical space and material resources and III - Health professionals, users, and the work process in the LCA. The decentralization of ACH to PHC has been shown to be effective and capable of producing more real leprosy indicators. However, several aspects related to the work process reduce the potential of PHC to control leprosy. The contributions of this review to practice include the identification of successful PHC practices in leprosy control and common weaknesses in the PHC work process, in addition to pointing out coping strategies based on the literature.